Bioanalysis Young Investigator: Richard A Scheltema. (June 2011) - Scheltema, Richard A; Breitling, Rainer
Supervisor''s supporting comments I would like to nominate Richard A Scheltema for the Bioanalysis Young Investigator Award 2011, for the work presented in his PhD thesis ''Surfing the Metabolome''. Richard has independently developed a computationally elegant and creative approach for dealing with the complex datasets generated by the new generation of high-resolution MS equipment. The novel methodologies developed in Richard''s thesis are collected in mzMatch, a pipeline of tools for the analysis and interpretation of metabolomics data. There is currently no other comparable tool for this increasingly important type of bioanalytical data. Richard''s key bioinformatics results were not only published in a number of important methodological papers, but are also available as open-source software on a community website (http://mzmatch.sourceforge.net ). Richard''s research has been very favorably received in the broader bioanalytics community: metabolomics researchers realize that his software is setting a new standard for the analysis of their complex datasets, exceeding available tools in reliability and quality of the results. The mzMatch tools developed by Richard are a central component of the analysis software of the Netherlands Proteomics-Bioinformatics Interface and are currently piloted for standardized use by the Dutch Metabolomics Centre. Currently, Richard is working as a postdoctoral researcher in the group of Matthias Mann (Munich), where he is applying his innovative ideas to the bioanalytics challenges faced in proteomics.